2021
DOI: 10.1021/acsaem.1c01534
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adverse Phase Transition at 4.2 V via increasing Cobalt Content on Ni-Rich Layered Cathode Materials

Abstract: Nickel-rich layered materials are the most commercially valuable power battery materials. However, because of the existence of Ni3+, lattice deterioration of nickel-rich ternary materials is especially serious in the cycle process. In this experiment, LiNi0.8–x Co0.1+x Mn0.1O2 is prepared by increasing the content of cobalt (x = 0.02, 0.04, 0.06). Through electrochemical test, X-ray diffraction analysis, galvanostatic intermittent titration technique, Rietveld refinement analysis, and other characterization me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Miraculously, the phase transition appears to be reversible with only a 0.15 V shift to the left, which appears to be the characteristic reduction peak unique to NCM-Ni82. 39 By observing the dQ•dV −1 curve (Fig. 5e) of NCM-HS, a core-shell particle without Al doping, it was found that the initial cycles do not have an obvious phase transition at approximately 4.2 V, but a reduction peak at approximately 4.05 V appeared after 50 cycles, which corresponded to the characteristic peak of NCM-Ni82.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Miraculously, the phase transition appears to be reversible with only a 0.15 V shift to the left, which appears to be the characteristic reduction peak unique to NCM-Ni82. 39 By observing the dQ•dV −1 curve (Fig. 5e) of NCM-HS, a core-shell particle without Al doping, it was found that the initial cycles do not have an obvious phase transition at approximately 4.2 V, but a reduction peak at approximately 4.05 V appeared after 50 cycles, which corresponded to the characteristic peak of NCM-Ni82.…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, the reduction in the content of Co (<10%) leads to the transformation of the layered phase into spinel phase and cation disorder. 37,38 In our previous work, 39 it was found that slight increases in the Co content can inhibit the unsteady phase transition and regulate the order of cations n Ni-rich layered materials at an SOC of 4.2 V. Corich materials bring unmatched optimization of structural and electrochemical properties to Ni-rich layered materials.…”
mentioning
confidence: 98%
“…In order to investigate the electrochemical behavior of cathode materials, the d Q d V –1 profiles of B-NCMA and A3-NCMA are obtained by differentiating the 1st/25th/50th/100th charge and discharge curves. As shown in Figure e,f, all curves exhibit three pairs of reversible redox peaks, which correspond to hexagonal-to-monoclinic (H1-to-M), monoclinic-to-hexagonal (M-to-H2), and hexagonal-to-hexagonal (H2-to-H3) phase transitions, respectively . Among these phase transitions, the H2-to-H3 phase transition triggers an abrupt contraction of the crystal in the c direction; thus, the crystal is inevitably subjected to intense mechanical strains, which destroy the crystal structure .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3e,f, all curves exhibit three pairs of reversible redox peaks, which correspond to hexagonal-to-monoclinic (H1-to-M), monoclinic-to-hexagonal (M-to-H2), and hexagonal-to-hexagonal (H2-to-H3) phase transitions, respectively. 49 Among these phase transitions, the H2-to-H3 phase transition triggers an abrupt contraction of the crystal in the c direction; thus, the crystal is inevitably subjected to intense mechanical strains, which destroy the crystal structure. 50 The H2-to-H3 phase transition peak intensity of the B-NCMA cathode gradually drops, indicating that the original structure does not recover completely and actually deteriorates during the cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical characterization.-There are three first-order phase transitions in high-nickel layered materials during charging. Some studies have shown that irreversible phase transition from hexagonal H2 to hexagonal H3 at 4.2 V. 28 When the charging voltage reaches 4.2 V, the battery is in a highly de-lithium state. Many Li + vacancies make the material structure become empty or even collapse, which hinders the diffusion rate of Li + .…”
Section: Analysis and Resultsmentioning
confidence: 99%